Choroba Sandhoffa oraz Tay Sachsa – w oparciu o przypadki własne - Kokot, Witold; Raczyńska, Krystyna; Krajka-Lauer, Jarosława; Iwaszkiewicz-Bilikiewicz, Barbara; Wierzba, Jolanta (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
The authors described two infant with Sandhoff's and Tay-Sachs disease. Tay-Sachs disease is well-known inherited disease leading to an accumulation of gangliosides in the brain and retina. Sandhoff's disease (GM2 gangliosidosis type 0) was diagnosed in an infant, in whom a progressive neurological disorder and cherry-red foveal spots were developed. In addition, to the general clinical examination, indirect ophthalnoscopy, blood white cells enzymatic examination are used to make definitive diagnosis. In this cases, the early eye fundus examination allowed us to make the proper diagnosis.